Riding the waves of success: unveiling the sports branding of the ASIAN beach games 2008 Bali - Muhammad Ikbar Ishomi (Jurnal Mantik, 2024)
Riding the Waves of Success: Unveiling the Sports Branding of the Asian Beach Games 2008 Bali" investigates the strategic and creative efforts behind the branding of the Asian Beach Games held in Bali in 2008. This research outlines the comprehensive approach taken to create a unique brand identity. different and memorable for the event, in line with the spirit of the game and Bali's unique cultural background. Through careful planning, innovative design, and effective communication strategies, branding initiatives. The research aimed to capture the essence of beach sports while showcasing the spirit and hospitality of Bali to a diverse international audience. This study uses a qualitative method. The research results provide insight into the key elements of the branding process, highlighting its impact in promoting the sport, fostering regional cooperation, and leaving a lasting impression on participants and spectators.